2018
DOI: 10.1002/tox.22531
|View full text |Cite
|
Sign up to set email alerts
|

Hinokitiol ablates myofibroblast activation in precancerous oral submucous fibrosis by targeting Snail

Abstract: Oral submucous fibrosis (OSF) is a precancerous condition with symptoms of limited mouth opening and areca nut chewing habit has been implicated in its pathogenesis. Hinokitiol, a natural tropolone derived from Chamacyparis taiwanensis, has been reported to improve oral lichen planus and inhibit various cancer cells. Here, we showed that hinokitiol reduced the myofibroblast activities in fBMFs and prevented the arecoline-induced transdifferentiation. Treatment of hinokitiol dose-dependently downregulated the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…In the last experiment ( Figure 6 C,D), we demonstrated that the knockdown of IL-6 hindered the myofibroblast activities in Snail-overexpressing cells. In addition to the direct binding of Snail to α-SMA [ 24 ], these results indicated that sufficient IL-6 was also required for Snail to induce myofibroblast activities. Along with the findings of Snail-regulated myofibroblast phenotypes, we showed that IL-6 may exert its fibrosis ability and elicit myofibroblast transdifferentiation via the modulation of numerous fibrosis factors and Snail in oral fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last experiment ( Figure 6 C,D), we demonstrated that the knockdown of IL-6 hindered the myofibroblast activities in Snail-overexpressing cells. In addition to the direct binding of Snail to α-SMA [ 24 ], these results indicated that sufficient IL-6 was also required for Snail to induce myofibroblast activities. Along with the findings of Snail-regulated myofibroblast phenotypes, we showed that IL-6 may exert its fibrosis ability and elicit myofibroblast transdifferentiation via the modulation of numerous fibrosis factors and Snail in oral fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Snail is sufficient to repress epithelial genes like E-cadherin by binding to E-box sequences through the zinc-finger domains [ 21 ]. As a matter of fact, the elevated expression of Snail has been found in various types of fibrosis [ 22 , 23 ] and our previous study revealed that Snail was able to bind to the E-box in the α-SMA promoter in buccal mucosal fibroblasts (BMFs) [ 24 ]. Moreover, it has been shown that arecoline increased Snail expression in human oral keratinocytes and the overexpression of Snail was proven to be associated with the clinico-pathologic features of OSCCs [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from these results, we demonstrated how butylidenephthalide interfered the arecoline‐induced activation of myofibroblasts. Our previous studies have shown that arecoline upregulated the expression of α‐SMA in BMFs via an increase in the binding of Snail to the α‐SMA promoter . Figure A illustrated the E‐box region in the promoter region of α‐SMA ([sbox]CAAATG[sbox], −498 to −493), and arecoline‐induced binding of Snail in α‐SMA promoter was significantly suppressed by butylidenephthalide treatment using chromatin immunoprecipitation (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…Given that our recent work has shown that Snail could bind to the E‐box region in the α‐SMA promoter, we examined whether butylidenephthalide impeded the direct binding of Snail on α‐SMA. In agreement with our hypothesis, butylidenephthalide inhibited the direct binding of Snail and ameliorated the activation of myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation